2014
DOI: 10.1007/978-1-4939-0897-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Pathways for Microbiome-Brain-Gut Axis Communication

Abstract: There is now strong evidence from animal studies that gut microorganism can activate the vagus nerve and that such activation plays a critical role in mediating effects on the brain and behaviour. The vagus appears to differentiate between non-pathogenic and potentially pathogenic bacteria even in the absence of overt inflammation and vagal pathways mediate signals that can induce both anxiogenic and anxiolytic effects, depending on the nature of the stimulus. Certain vagal signals from the gut can instigate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
298
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(304 citation statements)
references
References 97 publications
0
298
0
6
Order By: Relevance
“…Toxic chemicals, such as nitric oxide, quinolinic acid and kynurenic acid, can also be stimulated for release by vagal signaling. These chemicals cause decreased function of nerve cells [29,30]. In fact, the gut microbiome and intestinal permeability has mounting evidence linking it to brain development, function and behavior, through the immune, endocrine and neural pathways [31].…”
Section: Vagal Stimulation and The Brain Gut Axis In Depressionmentioning
confidence: 99%
“…Toxic chemicals, such as nitric oxide, quinolinic acid and kynurenic acid, can also be stimulated for release by vagal signaling. These chemicals cause decreased function of nerve cells [29,30]. In fact, the gut microbiome and intestinal permeability has mounting evidence linking it to brain development, function and behavior, through the immune, endocrine and neural pathways [31].…”
Section: Vagal Stimulation and The Brain Gut Axis In Depressionmentioning
confidence: 99%
“…The microbiota and the increase in permeability may also interact through the enteric tract with the vagus nerve. 29 It may affect the stress system. 30 Finally, it generates a mild form of chronic inflammation, related to the increased gut permeability, 31,32 that is currently considered an important factor for the development of depression.…”
Section: A Role For Dysbiosis In the Negative Reinforcement Processmentioning
confidence: 99%
“…Bravo et al reported that gut microbial dysbiosis can influence the function of the gut-brain axis via the vagus nerve and metabolites (3,4). As a result, the brain may release mediators, causing further immune modulation dysfunction, and activate inflammation through interaction with immune cells (5).…”
Section: To the Editormentioning
confidence: 99%